A communicative approach to conflict, forgiveness, and reconciliation reimagining our relationships - Kelley, Douglas L.; Waldron, Vincent R.; Kloeber, Dayna N. (Routledge, 2019)
"A Communicative Approach to Conflict, Forgiveness, and Reconciliation: Reimagining Our Relationships synthesizes communication and psychology scholarship that focuses on rebuilding ourselves and our relationships when things go "wrong". It provides fresh insights into the burgeoning body of forgiveness research, with an emphasis on community applications and reconciliation. Written by award winning scholars in forgiveness communication, the book makes forgiveness and reconciliation research accessible to students in courses focused on personal relationships, conflict, and family studies"--Provided by publisher.